THE EFFECT OF COUNTRY OF ORIGIN IMAGE TROUGH QUALITY, DESIGN AND ATTRACTIVENESS RELATED TO PRODUCT ON CONSUMER LOYALTY - Šapić, Srđan; Lazarević, Jovana; Filipović, Jovana (The European Journal of Applied Economics, 2021)
The main goal of this research is to determine whether there is an impact of country of origin image on consumer loyalty to products originating from countries with positive and recognizable image and whether this impact is achieved through characteristics such as product quality and design, and attractiveness related to using the same. To examine this impact, an empirical study was conducted on a sample of 150 respondents and analysis of collected data was performed in SPSS 20. The results show that information about country of origin image is important to consumers and has an impact on their behavior related to buying foreign product. More precisely, results show that country of origin image affects consumers when they choose products based on their quality and design and attractiveness that consumers feel when using these products, and also that through these characteristics country of origin image has effects on consumer loyalty. In accordance with the obtained results, conclusion is that it is extremely desirable for companies and governments to take into account image that their country enjoys on the world market.
Keywords: country of origin image, product quality, product design, attractiveness, consumer loyalty